SAT0117 Retention rates of adalimumab, etanercept, and infliximab as 1st- or 2nd-line biotherapy for rheumatoid arthritis patients in daily practice in auvergne. (15th June 2017) - Soubrier, M; Pereira, B; Frayssac, T; Fan, A; Couderc, M; Malochet-Guinamand, S; Mathieu, S; Tatar, Z; Tournadre, A; Dubost, J-J
Abstract : Background: The use of anti-tumor necrosis factor-alpha agents, or anti-TNFs, has greatly improved the treatment of rheumatoid arthritis (RA). The first three anti-TNFs available to us (infliximab, adalimumab, and etanercept) are the most widely used in treating RA. Their efficacy and safety, demonstrated in extensive randomized and controlled trials (RCTs), were not shown to vary significantly when compared indirectly based on randomized studies. Nevertheless, the randomized studies were of short duration and included a selected population that differed from patients treated in daily practice. Objectives: To compare, in real-life conditions, the retention rates of the initial anti-TNF treatment (etanercept [ETN], adalimumab [ADA], and infliximab [IFX]) initiated as first-line biotherapy for rheumatoid arthritis (RA) and to evaluate, in case of failure, the switch to another anti-TNF or a non-anti-TNF biological. Methods: Monocentric retrospective cohort including all patients with RA starting a first anti-TNF between 2001 and 2015. Results: Among the 346 patients analyzed, 201 received ETN, 82 ADA, and 63 IFX. The first anti-TNF was interrupted in 151 cases. The retention rates were 82.8%, 67.6%, 46.5%, 28.1%, and 22.5% at 1, 2, 5, 10, and 15 years, respectively, with a median retention duration of 52.8 [18.9 -136.2] months (ETN: 59.3 [19.1-NA), ADA: 79.9 [19.3–136.2], and IFX: 37.2 [17.5–134.5], p=0.49). The predictive factors of discontinuation were active RA (DAS28-CRP HR: 1.22 [1.03–1.45]), inflammatory syndrome (ESR HR: 1.01 [1.0–1.02]; CRP HR: 1.00 [1.00–1.01]), absence of MTX treatment (HR: 0.60 [0.43–0.83]), and corticosteroid use (HR: 1.91 [1.31–2.78]). The patients who switched to another anti-TNF treatment had an inferior retention than those who switched to a non-anti-TNF treatment (HR: 0.39 [0.17 - 0.87], p: 0.02). p=0.02). Conclusions: In real life, there was no difference in retention among the three anti-TNF agents, and 25% of patients continued them at 15 years. After failure of an anti-TNF, the switch to a non-anti-TNF biotherapy showed better retention. Disclosure of Interest: None declared